O mix de recompensas no contexto da pandemia de covid-19: um levantamento na região de Sorocaba – SP - Amaral, Nattan Prochnon; Chueri, João Carlos Tecchio (Universidade Federal de São Carlos, 2021)
The COVID-19 pandemic caused many impacts, either on the personal life or in the professional life, they are undeniable. Still, due to it being a recent event, these impacts are yet to be fully measured. The objective of this article is to bring light upon which changes have taken place in the perception of the rewards mix due to the pandemic scenario in the region of Sorocaba. The research method employed was Survey, for a quantitative and descriptive exploration, having as its desired public the mass of workers in the region of Sorocaba which could participate through an online form. The data was analyzed through the comparison of the answers and the ranking, which allowed evidencing the changes suffered in the desired mix, confirming the idea that the pandemic would impact this perception of the workers, as well as signalizing the growth of the value of autonomy compared to the others elements of the mix.
The rewards mix in the covid-19 pandemy context: a survey in the region of Sorocaba - SP
Keywords: Mix de Recompensas; Remuneração; Survey; Covid 19; Rewards Mix; Compensation; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DE RECURSOS HUMANOS